Implementation of Accountability and Responsibility in Governance Structure on Village Owned Enterprises - Desak Made Mya Yudia Sari; Ida Ayu Nirma Prameswari (Business Review and Case Studies, 2023)
The study intends to show data that can be explained comprehensively to improve the performance of village owned enterprises Wija Sari in Samsam Village, protect stakeholders, and improve compliance with regulations and generally accepted ethical values in implementing the banking industry guided by good governance, especially the governance structure. Collecting qualitative data in this study used documentation, observations, and interviews with an interpretive approach. The results of the research state that accountability disclosure is an obligation of liability that must be achieved by applying the principles of transparency, accountable, and sustainability, while disclosure of responsibility whose obligation to be responsible to stakeholders applies cooperative, participatory, and emancipatory principles. Keywords: banking industry, accountability disclosure, governance structure, village owned enterprises